Relationship between small ruminants behaviour and landscape features in Northeast of Portugal - Castro, Marina (2012)
﻿In Northeast Portugal, most small ruminant production is an extensive activity based on grazing itineraries. The shepherds direct their flocks on daily grazing itineraries across different patches of landuse. The study of livestock activities permits understanding the animal’s perception of landscape. Animal activities (grazing, resting and walking) were also affected by landscape attributes. The aim of the study was to examine the relationships between livestock behavior and landuse types, and to check how they change throughout the year and the time of day (temperature and vegetation moisture effect). Having an understanding of animal landscape use could help to develop strategies to better management the landscapes and its temporal changes.